Analisis Faktor Faktor Penentu Keberhasilan Atlet Jujitsu Gresik Kelas Newaza Dalam Pekan Olahraga Provinsi (PORPROV) - Milkhatil Arofah; Achmad Widodo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The sport of jujitsu has gained significant popularity among the fighting community and martial arts athletes, including Gresik athletes. Although jujitsu has been around for centuries, the sport has experienced rapid growth in recent years, often taking part in some of the most prestigious martial arts competitions, including the Provincial Sports Week (Porprov). In a broader context, this research can also contribute to existing literature on the factors that influence athlete performance in the Gresik jujitsu martial arts sport. This research is a type of quantitative research. The research design used is a qualitative cross-sectional which allows researchers to study and evaluate the characteristics of various research subjects at a certain poin in time, in this case the assessment was carried out at the PORPROV time. This research was conducted in various places related to the activities of Jujitsu athletes, including their training grounds and the Provincial Sports Week (PORPROV) competition locations. The population in this study was a Gresik Jujitsu athlete who competed in the women's Newaza system class category in the Provincial Sports Week (PORPROV). The population in this study was a Gresik Jujitsu athlete who competed in the women's Newaza system class category at the Provincial Sports Week. . The sample in this study included a number of Jujitsu Gresik athletes taken purposively, their coaches and other supporting parties. There are three research instruments used, namely; interviews, observations, and document searches. In analyzing qualitative data, this research will adopt the Miles and Huberman data analysis model which consists of three main stages: data reduction, data presentation, and drawing conclusions. From the results of the interview, internal factors show that the athlete has high motivation and is physically fit, but it is unfortunate that his mental state is not good, where during the interview the athlete felt nervous, inferior and countered in the final round. Not only that, external factors also include coaches who are very supportive and also feel the nervousness that athletes feel. From the results above, there are two factors determining the success of jujitsu athletes in Gresik district, namely internal factors and external factors. Internal factors include the athlete's self-motivation, mental and physical characteristics. Meanwhile, external factors can come from official support, parents, the environment, as well as facilities and infrastructure.